Age-Related Differences in Executive Functions Within High-Level Youth Soccer Players - Beavan, Adam Francis; Spielmann, Jan; Mayer, Jan; Skorski, Sabrina; Meyer, Tim; Fransen, Job (Brazilian journal of motor behavior, 2019)
Background: When measuring executive functions (EF), it is common for athletes to be assessed on their ability to detect and process explicit sources of information. Yet not all of the information is perceived explicitly in an environment. Aim: This study aimed to include a new assessment that measures the impact of implicitly perceived congruent and incongruent visual precues on response times. Method: Seventy-four male soccer players: U12 (n=15), U13 (n=17), U17 (n=21) and U19 (n=21) representing a German 1st league club were assessed on four cognitive tasks. Results: The MANOVAs revealed a multivariate effect of age group on a reactive stress tolerance task (F(6,140)=11.670, p<0.001, ES=0.38) and a Stop Signal Reaction Time task (F(6,144)=6.142, p<0.001, ES=0.20). A one-way ANOVA revealed an age group effect for response accuracy in a multiple-object-tracking task (F(3,74)=4.05, p=0.01, ES=0.14). Lastly, a within-subjects effect of congruency on the implicit precued task (F(1,74)=51.32, p<0.001, ES=0.41) and a between-subjects effect of age group (F(3,74)=4.30, p=0.008, ES=0.15) was observed. Interpretation: The results provided support for including an implicit precueing task, while the overall testing demonstrated that the magnitude of the increase in EF performance between ages was greater across the younger age groups compared to the older age groups.